Sistem Informasi Kepemudaan Kabupaten Sijunjung berbasis Web - Qorina Zaer; Asril; Efri Yandani S (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The lack of information and data available at the Youth and Sports Tourism Office in the field of Youth and Sports makes it difficult for people to access information about youth. The data currently available is deemed inadequate because the data is only in the form of numbers, so the need for relevant, accurate, timely and integrated data and information to be presented to the public. For this reason, the development of a Web-Based Youth Information System is expected to facilitate related parties in meeting the data and information needs of the community. The development of this system is designed using the PHP, Javascript, CSS, and Jquery programming languages. While the model used in making this system uses the waterfall method. So that the system built can be utilized and useful for the Youth and Sports Office, researchers conduct direct observations in the field to collect the data and information needed and conduct direct interviews with the Youth and Sports Tourism Office to find out the form of the system needed. With the use of communication and information technology in the form of this website, it is hoped that it will facilitate the Sijunjung Regency Youth and Sports Tourism Office in providing accurate and precise information and data and encourage the creation of transparency in the administration of government.